(untitled) (Journal of Bangladesh Academy of Sciences, 2026)
This study investigates the self-aggregation of dodecyltrimethylammonium bromide (DTAB) and triton X-100 (TX-100) with bovine serum albumin (BSA) in absence and presence of monohydroxy organic compounds such as ethanol (EtOH) and 1-propanol (1-PrOH) by means of conductivity and UV-visible spectroscopic methods. The binding and partitioning of BSA with TX-100 micellar media were also explored through UV-visible spectroscopic tool. The critical micelle concentration (CMC) values of the studied surfactants were found to be strongly dependent on the BSA concentration, chain length of alcohols, solvent composition as well as on temperature. The CMC values of DTAB + BSA and TX-100 + BSA mixtures were notably higher in aqua-alcohols media compared to those values of the mixtures in aqueous medium. The greater values of binding constant (kb), partition constant (Kc) and partition coefficient (Kx) of TX-100 and protein mixture revealed the stronger binding and significant partitioning of BSA in TX-100 micellar media. The values of free energy changes (ΔGm o / ΔGb o/ΔGp o ) were achieved to be negative which indicated the spontaneous micellization/binding/partitioning of the studied systems. The values of enthalpy (ΔHm o ) and entropy changes (ΔSm o ) for the DTAB + BSA mixture in both aqueous and aqua-alcohols media indicated that the micellization of the system was predominantly an entropy-driven process at lower temperatures, which became both enthalpy and entropy controlled process at higher temperatures. The results of the study showed significant effects of the composition of aqua-alcohol mixed solvents and temperatures on the investigated mixtures for optimizing micellar systems in pharmaceutical and biochemical applications. J. Bangladesh Acad. Sci. 50(2); 329–346: June 2026